Remote Monitoring and Control System for Solar Drying Based on ATMega 2560 and LoRa Technology - Ortiz-Rodríguez, Néstor; Águila León, Jesús; Lucero-Tenorio, Miriam; Villaseñor Correa , Jesús F. (EASI: Engineering and Applied Sciences in Industry, 2025)
Sun drying is an effective technique for food preservation, although it presents significant challenges in optimizing and controlling its variables. This paper describes the development of a remote control, data acquisition and monitoring module designed to optimize solar drying processes. The system uses a customized electronic board based on the ATMega 2560 microcontroller, which integrates LoRa technology for remote data storage and monitoring. The development of the module was structured in three main phases. The first step was a proof-of-concept operation with an Arduino Mega development board, which tested the control and central control concepts. Secondly, after identifying the need for increased durability and stability, a custom table was designed using CAD software and Bakelite copper to improve the durability and reliability of the system. Finally, in the third step, the final version of the tabletop, adapted to the drying conditions of the sun, was printed and assembled. The developed module can be adapted to operate on different types and scales of solar dryers, and, being built with low-cost devices, it is an affordable solution for the control and monitoring of this type of process. This solution has potential to improve the efficiency of drying processes for various contexts.
Keywords: Control and monitoring; Process optimization; Solar drying; LoRa; ATMega 2560; renewable energy